World Health Organization Tool for Benchmarking Ethics Oversight of Health-Related Research with Human Participants - Namita Ghimire; Rojina Basnet; Richa Acharya; Santoshi Adhikari; Shashi Verma; Mohan Raj Sharma (Journal of Nepal Medical Association)
Benchmarking ethics oversight is a process of aligning comparing and evaluating the strengths and room for improvement of ethical review and approval process across different institutions or the country. The World Health Organization tool for benchmarking ethics oversight is designed to help countries assess and improve their systems for ethically overseeing health-related research involving human participants. It identifies gaps in legal frameworks, committee structures, resources, accountability and transparency while promoting best practices and policy alignment. Nepal has made progress through the research regulations body like the Nepal Health Research Council , but challenges such as inconsistent implementation, oversight of the implementation and resource limitations remain. The tool offers an opportunity to strengthen Nepal’s health research governance and regulation but it must be adapted to fit local contexts, emphasizing accountability, transparency, capacity-building, and improved communication.